Comparison of glucocorticoids and painkiller prescribed days between rheumatoid arthritis patients receiving early and late treatment with a biological agent via a population-based cohort study. Issue 47 (25th November 2022) - Lee, Zon-Min; Yang, Yao-Hsu; Kuo, Ho-Chang; Shen, Ya-Han; Yu, Hong-Ren; Su, Yu-Jih
Abstract : Comparison between early biologics treatment and late biologics treatment of rheumatoid arthritis (RA) patients in decreasing prescription days of glucocorticoids and painkillers by using the Taiwan National Health Insurance Research database from January 1, 1997 to December 31, 2013. We defined early use of biologics as biologics prescribed within 2.24 years after the RA diagnosis, and the late use of biologics was defined as those prescribed after 2.24 years of the RA diagnosis. These definitions are based on previous studies defining early arthritis as arthritis within 2 years of diagnosis, while we needed another 3 months for application biologics here in Taiwan, which equals a total of 2.24 years. Among the 821 patients, 410 patients (50%) were classified in the Early group, and the other 411 patients (50%) were classified in the Late group. The use of any of these 3 types of medication, including steroids, disease modifying antirhuematic drugs, and nonsteroid anti-inflammatory drug (NSAID) was changed significantly after biologics treatment. Comparing between before and after biologics treatment, oral medication was significantly tapered (all P  < .0001). The results show that men are 1.81 times more likely than women to taper oral glucocorticoids and NSAIDs. Younger age (<45) patients are 1.91 times more likely to taper steroids and NSAIDs than those aged over 65 years old. Both gender and age were found to be independent factors that could decrease days of prescription of both steroids and NSAIDs in early use of biologics agents. This study indicates that younger patients only need short-term (2.53 ± 1.92 years, P  = .03) and early treatment with biologics (within 2.24 years of diagnosis of RA), just in order to taper steroids and NSAIDs to less than 50% compared to the steroids and NSAIDs doses before biologics treatment.